Habitat preference of Viminella flagellum (Alcyonacea: Ellisellidae) in relation to bathymetric variables in southeastern Sardinian waters. (15th April 2017) - Giusti, M.; Bo, M.; Angiolillo, M.; Cannas, R.; Cau, A.; Follesa, M.C.; Canese, S.
Abstract: The whip-like gorgonian Viminella flagellum (Alcyonacea, Ellisellidae) has an Atlantic-Mediterranean distribution. In Italian seas, the species is a common component of deep-sea rocky environments from the north-western Mediterranean area to the Strait of Sicily. V. flagellum grows in deep habitats, sometimes outlining the environment with dense forests. This work describes its habitat in an area in the southeastern Sardinian waters (central-western Mediterranean Sea), where a dense forest of the species was found. The specimens were filmed and photographed between 120 and 260 m depth with a Remotely Operated Vehicle (ROV). High-resolution multibeam echosounder (MBES) bathymetry data of the area were acquired and morphometric parameters were derived. These parameters were assumed to be relevant for the distribution of the whip-like gorgonians and were used in an Ecological Niche Factor Analysis (ENFA) to explore the niche and habitat preference of the target species. In order to identify which Eco-geographical variables are useful to predict coral distribution, we used the Maximum Entropy model (MaxEnt). Our results gave a first description of the habitat preference of V. flagellum . Specimens were found in a distinctive habitat, with respect to the overall features of the entire studied area which was characterised by a marked slope in a simple rocky seabed system, within a water depth range of 125–150 m. Highlights: An ENFA and a MaxEnt model were used to model the habitat of the whip-like gorgonian Viminella flagellum . The habitat preference of the species was identified. The species' probability of occurrence was mapped.